2021
DOI: 10.3390/molecules26092678
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Stability of Methylammonium Lead Iodide (MAPbI3) Film Doped with Lead Cesium Triiodide (CsPbI3) Quantum Dots under an Oxygen Plasma Atmosphere

Abstract: In this study, we describe composited perovskite films based on the doping of lead cesium triiodide (CsPbI3) quantum dots (QDs) into methylammonium lead iodide (MAPbI3). CsPbI3 QDs and MAPbI3 were prepared by ligand-assisted re-precipitation and solution mixing, respectively. These films were optimized by oxygen plasma treatment, and the effect of powers from 0 to 80 W on the structural properties of the composited perovskite films is discussed. The experimental results showed that the light-harvesting ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Furthermore, it is shown that oxygen is a method to suppress nonradioactive recombination and to improve the photovoltaic performance [ 24 ]. The plasma treatment also caused the decrease in the grain boundary of the MAPbI 3 film, which can be seen in a previous study [ 10 ]. With the decrease in the grain boundaries, the scattering of charge carriers reduced and the mobility of the film increased [ 25 ].…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…Furthermore, it is shown that oxygen is a method to suppress nonradioactive recombination and to improve the photovoltaic performance [ 24 ]. The plasma treatment also caused the decrease in the grain boundary of the MAPbI 3 film, which can be seen in a previous study [ 10 ]. With the decrease in the grain boundaries, the scattering of charge carriers reduced and the mobility of the film increased [ 25 ].…”
Section: Resultssupporting
confidence: 73%
“…In Table 1 , the mobility of the MAPbI 3 doped with CsPbI 3 QDs was higher than that of the pure MAPbI 3 film. The stability could be improved by doping with CsPbI 3 QDs, and the number of defects on the film can be decreased, leading to the higher mobility [ 10 ]. For the analysis of the conduction mechanism, the mobility and the carrier concentration were measured through Hall effect measurement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations